Bibliotherapy Sebagai Sebuah Teknik dalam Layanan Bimbingan dan Konseling - Asep Solikin (Anterior Jurnal, 2015)
Bibliotherapy as a technique in the activities of guidance and counseling services at the moment is becoming a necessity in the world where both readings based information in the form of digital print out or have been so familiar with the people who are also experiencing problems in the individual development of their social life . Bibliotherapy often referred to reading theraphy, which is in the process someone who is having problems asked to read books that are helping themselves and motivate in order to promote healing. Read about the difficulties others similar to them, can provide awareness and understanding of the problems faced. This research use descriptive approach or describing a problem based on literature review of existing literature or books in accordance with the guidelines of this study. In the implementation of this paper focuses on the study of literature study using historical study (Dirasat al - Tarikhiyah), which is trying to trace the concepts biblioteraphy, through studies and sources of books on therapy that are relevant to the discussion of this study . Reading activities in bibliotherapy uses age-appropriate books in the treatment and therapy is usually followed by discussions on the topic of life issues in accordance with the experienced conditions. Bibliotherapy is used by school counselors, social workers, health nurses, teachers and librarians. The use of the book as a therapy to support the needs of children in the process information to increase understanding and raise awareness of the problems experienced.